Swept-Source Optical Coherence Tomography-Based Biometry: A Comprehensive Overview - Alfredo Borgia; Raffaele Raimondi; Tania Sorrentino; Francesco Santoru; Matilde Buzzi; Vittorio Borgia; Vincenzo Scorcia; Giuseppe Giannaccare (Photonics, 2022)
The purpose of this study was to summarize the results related to ocular biometry performed using swept-source optical coherence tomography (SS-OCT). A literature search was conducted to search articles reporting the clinical outcomes of patients who underwent examinations with commercially available SS-OCT machines. The available data were thoroughly analyzed, with a particular focus on all the biometric factors used to calculate the power of intraocular lenses (IOLs) implanted during cataract surgery. The agreement, repeatability, and reproducibility of several parameters among different devices were examined. The variations found for parameters obtained from agreement testing were evaluated in order to promote the interchangeability of devices. Swept-source optical coherence tomography biometers usually produce highly repeatable and reproducible results. The excellent results obtained led us to the conclusion that optical biometers based on SS-OCT technology will probably take the lead in ocular biometry.